Recovering Investor Expectations from Demand for Index Funds - Egan, Mark; MacKay, Alexander; Yang, Hanbin (Review of Economic Studies, 2022)
Abstract We use a revealed-preference approach to estimate investor expectations of stock market returns. Using data on demand for index funds that follow the S&P 500, we develop and estimate a model of investor choice to flexibly recover the time-varying distribution of expected future returns across investors. Our analysis is facilitated by the prevalence of leveraged funds that track the same underlying asset: by choosing between higher and lower leverage, investors trade off higher return against less risk. Our estimates indicate that investor expectations are heterogeneous, extrapolative, and persistent. Following a downturn, investors become more pessimistic on average, but there is also an increase in disagreement among participating investors due to the presence of contrarian investors.